circlize implements and enhances circular visualization in R - Gu, Zuguang; Gu, Lei; Eils, Roland; Schlesner, Matthias; Brors, Benedikt (Bioinformatics (Oxford, England), 2014)
Circular layout is an efficient way for the visualization of huge amounts of genomic information. Here we present the circlize package, which provides an implementation of circular layout generation in R as well as an enhancement of available software. The flexibility of this package is based on the usage of low-level graphics functions such that self-defined high-level graphics can be easily implemented by users for specific purposes. Together with the seamless connection between the powerful computational and visual environment in R, circlize gives users more convenience and freedom to design figures for better understanding genomic patterns behind multi-dimensional data. Availability and implementation:  circlize is available at the Comprehensive R Archive Network (CRAN): http://cran.r-project.org/web/packages/circlize/ Contact:  b.brors@dkfz.de Supplementary information:  Supplementary data are available at Bioinformatics online.